High-fat diet-induced dyslipidemia drives retinal ECE-1 and ET-1 upregulation - Sun, Shuo; Zhang, Huilan; Chen, Jing; Hei, Kaiwen; Hou, Yi; Yang, Yanhui; Shan, Chunyan; Zhang, Longli (Frontiers in Endocrinology, 2025)
BackgroundHigh-fat diet (HFD) consumption is a major contributor to metabolic disorders, including obesity, dyslipidemia, and endothelial dysfunction, which have systemic and ocular consequences. Emerging evidence suggests that metabolic disturbances can lead to retinal pathology, but the underlying mechanisms remain unclear. Endothelin-1 (ET-1) and its regulatory enzyme, endothelin-converting enzyme-1 (ECE-1), play critical roles in vascular dysfunction. However, their involvement in HFD-induced retinal changes has not been fully elucidated.MethodsWe used a mouse model of HFD-induced metabolic dysfunction and assessed systemic metabolic parameters, including lipid profiles, liver function markers, and inflammatory cytokines. Retinal gene expression of inflammatory and vascular factors, including ET-1 and ECE-1, was quantified using qPCR. Correlation analyses were performed to evaluate the relationship between systemic metabolic alterations and retinal molecular changes.ResultsHFD feeding led to significant metabolic disturbances, including increased body weight, elevated total cholesterol (TC) levels, and hepatic stress. Retinal analysis revealed a significant upregulation of pro-inflammatory cytokines (IL-1β, IL-6, TNFβ1, and TNFSF15), as well as increased expression of ECE-1 and ET-1. Notably, correlation analysis demonstrated a strong positive association between TC levels and retinal ECE-1 (Pearson’s r = 0.888, p = 0.018*) and ET-1 (Pearson’s r = 0.815, p = 0.048*), suggesting a mechanistic link between systemic dyslipidemia and retinal vascular dysfunction.ConclusionOur findings provide compelling evidence that HFD-induced dyslipidemia is associated with retinal inflammation and endothelial dysfunction, with ECE-1 and ET-1 serving as key mediators. These results highlight a potential therapeutic target for preventing retinal complications associated with metabolic disorders.